Withaferin A protects against hyperuricemia induced kidney injury and its possible mechanisms. Issue 1 (1st January 2021) - Zhao, Xia; Wang, Jing; Tang, Liying; Li, Pei; Ru, Jing; Bai, Yuzhi
ABSTRACT: The study was designed to explore the effects of Withaferin A (WFA) on hyperuricemia-induced kidney injury and its action mechanism. Potassium oxonate (PO) was employed to establish the hyperuricemic mouse model. The pathological changes of renal tissue were evaluated by hematoxylin-eosin and masson trichrome staining. The levels of creatinine, blood urea nitrogen (BUN), uric acid (UA) and xanthine oxidase (XOD) were detected using corresponding commercial kits. Expressions of collagen-related and apoptosis-associated proteins in renal tissues were, respectively, evaluated by immunofluorescence and western blotting. Cell apoptosis was detected by TUNEL assay, and transporter expressions using western blotting. Followed by WFA, NRK-52E cells were treated with UA before evaluation of apoptosis and fibrosis. Results indicated that WFA ameliorated renal damage, improved kidney function, and decreased levels of creatinine, BUN, UA, and XOD in PO-induced hyperuricemic mice. Furthermore, WFA significantly prevented renal fibrosis and increased the expression of collagen-related proteins. Similarly, WFA markedly inhibited renal apoptosis, accompanied by changes of apoptosis-related proteins. Importantly, expression of transporters responsible for the secretion of organic anion transporter 1 (OAT1), OAT3, ATP-binding cassette subfamily G member 2 (ABCG2) was remarkably enhanced whereas that of urate transporter 1 (URAT1) and glucose transporter 9 (GLUT9) was reduced in renal tissues of mice with hyperuricemia. In vitro study revealed that WFA notably ameliorated UA-induced cell fibrosis and apoptosis. Taken together, WFA improves kidney function by decreasing UA via regulation of XOD and transporter genes in renal tubular cells. Graphical abstract: uf0001